Association Between Neuropsychiatric Symptoms and Blood‐Based Autoantibody Biomarkers. (20th December 2022) - Emrani, Sheina; DeMarshall, Cassandra; Viviano, Jeffrey; Godsey, George; Sarkar, Abhirup; Belinka, Benjamin; Libon, David; Nagele, Robert
Abstract: Background: Neuropsychiatric symptoms are frequently observed along the Alzheimer disease (AD) continuum. Recent research has shown that blood‐based biomarkers are able to identify early AD‐related pathological changes associated with (1) preclinical AD (before the onset of clinical/functional symptoms), (2) mild cognitive impairment (MCI; with clinical symptoms and relatively spared functional decline), and (3) AD (obvious clinical and functional symptoms). Evidence for the potential diagnostic utility of serum autoantibodies has been extensively studied. The purpose of this study is to explore whether blood levels of specific autoantibodies used in the diagnostic biomarkers panels are linked with specific behavioral changes observed along the AD continuum. Method: Using a customized panel of three AD‐specific autoantibody biomarkers and Luminex xMAP® technology, sera from patients (n=46; female = 30, mean age = 73.4) from the Memory and Aging Program at Rowan University were analyzed. All patients, irrespective of diagnosis (cognitively normal, MCI, AD) were included. The Neuropsychiatric Inventory (NPI) was used to gather data pertaining to neuropsychiatric symptoms. Partial correlations, controlling for age and education, for each neuropsychiatric symptom was employed. Result: Two of the three autoantibody biomarkers showed an association with neuropsychiatric symptoms. Biomarkers 2 and 3 both showed a significant correlation with total neuropsychiatric score (r= .255, p= .047; r= .345, p= .01, respectively). Delusions, hallucinations, depression, anxiety, and irritability symptoms were not associated with either biomarker. Biomarker 2 was associated with apathy (r= .365, p=.007), agitation (r= .345, p= .011), disinhibition (r=.316, p=.018), and appetite changes (r= .302, p= .023). Biomarker 3 was associated with elation (r= .328, p= .015), aberrant motor behaviors (r= .331, p=.014), sleep behaviors (r= .483, p=.001), and appetite changes (r= .372, p=.006). Conclusion: Results demonstrate an association between neuropsychiatric symptoms often observed in the AD continuum and specific blood‐based autoantibody biomarkers using Luminex xMAP® bead‐based technology. The autoantibody biomarker panel serves as an accurate, non‐invasive, and inexpensive diagnostic screener for preclinical AD, MCI, and AD. These biomarkers can not only distinguish different stages of AD, typically diagnosed using cognitive/functional assessments, increased blood levels of specific autoantibody biomarkers are also associated with commonly observed neuropsychiatric features.